Associations between geography, decision‐making style, and interest in cancer clinical trial participation. Issue 22 (16th September 2022) - Caston, Nicole E.; Williams, Courtney P.; Wan, Clara; Ye, Star; Pywell, Cameron; Ingram, Stacey A.; Azuero, Andres; Sussell, Jesse; Patel, Shilpen; Arend, Rebecca; Rocque, Gabrielle B.
Abstract : Background: Clinical trials offer novel treatments, which are essential to high quality cancer care. Patients living in rural areas are often underrepresented in clinical trials due to several factors. This study evaluated the association between rurality and interest in clinical trial participation, change in interest, and treatment decision‐making style preference. Methods: This cohort study included patients with cancer receiving oncology care at the University of Alabama at Birmingham from 2017 to 2019. Associations between treatment decision‐making preference and the interaction between rurality and area deprivation were analyzed using multinomial logistic regression. Initial interest in clinical trial participation and change in interest were analyzed using modified Poisson regressions with robust standard errors. Initial interest model was stratified by Area Deprivation Index (ADI; higher vs. lower disadvantaged). Results: In adjusted models, patients in rural versus urban areas had similar initial interest in clinical trials, both those in higher (40% vs. 50%) and lower disadvantaged settings (54% vs. 62%). Additionally, rural versus urban patients had similar change of clinical trial interest for both those who changed from uninterested‐to‐interested (31% vs. 26%) and interested‐to‐uninterested (47% vs. 42%). Conclusion: This study compares the interest in clinical trial participation among patients living in rural and urban settings. Lack of interest may be secondary to barriers that patients in rural areas face (e.g., transportation, financial, access). Most rural patients prefer a shared treatment decision‐making style, which should be considered when identifying interventions to increase enrollment of underserved rural patients in clinical trials. Abstract : Cancer clinical trials are important to advancing cancer care; however, patients residing in rural areas are often underrepresented and reasons are multifactorial. When compared to urban patients, rural patients living in higher and lower disadvantaged areas had similar interest in clinical trials and similar change in interest.